Larangan Menikah Bagi Calon Mempelai yang Masih dalam Masa Studi di Secanggang Kab. Langkat Perspektif Maqashid Syariah - Albaz, Muhammad; Hayati, Amal (LPPM Universitas Ekasakti Padang, 2023)
This study aims to (1) find out the factors behind the ban on marriage for prospective brides who are still in education and (2) find out the analysis of sharia maqashid related to the ban on marriage while still in the study period. This study was designed with qualitative methods to be able to explain in detail about the prohibition of marriage while still in education. This research is a type of field research that takes references from books whose subjects prohibit marriage. While the object of this study is the bride and groom who are prohibited from marrying while still in education. To collect data, researchers use reading techniques and then record the results. While the analysis technique is descriptive. The results of this study are: The ban on marriage made by parents is only temporary and not eternal, so it is in accordance with the order of Maqashid Sharia, namely hifz aqli (maintaining reason / science) both religious science (ukhrawi) and knowledge (worldly) obtained by learning the main. With Science will be fulfilled another primary need. Seeking knowledge in Islam is compulsory for every Muslim, it is contained in the Qur'an and Hadith. Then the background of the ban on marriage for brides who are in the study or education period, one of the factors is the concern of the elderly about the future of their children, the economy, social norms and factors of the development of the times and technology that is growing rapidly.